Development of a special interface element between brick and plate bending elements - Kohnehpooshi, Omid; Noorzaei, Jamaloddin; Jaafar, Mohd Saleh; Muhammad Rashid, Raizal Saifulnaz (Elsevier, 2011)
In this study a special three-dimensional interface element has been formulated for stress and displacement analyses in bonded joint between two adjacent plate bending and brick elements. Interface element has 16 nodes with 5 degrees of freedom in each node adjacent to plate bending element and 3 D.O.F in each node adjacent to brick elements. The interface element has ability to transfer three translations from each side of interface element and two more rotations in the side adjacent to the plate element. Stiffness matrix of this element was formulated and implemented in three dimensional finite element code. Using experimental and numerical work of strengthened RC concrete beams carried out by researchers, application of this element including variation of deflection, slip between plates and bricks, normal and shear stresses distributions in FRP plates have been verified. The results show, that this interface element is effective and can be used for structural components with this type of interface element.